Daya Dukung Model Kelompok Tiang dan Block Foundation Dengan Variasi Panjang dan Spasi Tiang - Soewignjo Agus Nugroho; Syawal Satibi; Subhan Pytar Wijaya; Yusuf Agustamar (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2023)
Analysis of bearing capacity for foundation design is important. Therefore, need an alternative design to know actual capacity of pile group and block. Models of pile group with variations in number, length, and spacing is used on uniform loose sand for proved it. The loading tests conducted on pile models and record p-y curve. The research aims to study effect of number, length, spacing of pile in piles group compared with pile capacity of block. Based on 25 mm settlement of loading test, the result shows block foundation, 3d and 5d spacing has capacity 1560N, 1200N, 1230N respectively on 400 mm length. Analysis of p-y curve with Chin methods, pile capacity of spacing 5d, 3d of pile group and block, in sequence, were 1380N, 1430N and 1660N. Hence, its can be concluded that the pile group in 3d spaced has a larger capacity than 5D spaced.